Effect of Lanthanum Doping on Modulating Thermochromic Properties of VO2 Thin Films - Wang, Ning (2016)
Lanthanum (La) doped vanadium dioxide (VO2) thin films were fabricated through a facile sol-gel technique. The La doping was found to be effective in reducing the phase transition temperature (τc) of VO2 below the 4 at.% doping level, with a reducing rate of -1.1 °C/at.%. In addition, below the 3 at.% La doping level, the band gap (Eg) decreased steadily with the increasing addition of La dopants. The 5 at.% La doping can enhance both integrated visible transmission (Tlum) and solar modulating ability (ΔTsol) simultaneously. The combination of Tlum=50.1% and ΔTsol=10.3% represents the best value for VO2 continuous thin films.